Integrasi Garis dan Sudut dalam Matematika dengan Nilai – Nilai Islam - Putra, Firnanda Pradana; Rifaldi, Rifaldi (Kaunia: Integration and Interconnection Islam and Science Journal, 2024)
Integrating or connecting mathematics with Islamic values can add to the treasures of knowledge and increase the level of our faith in Allah SWT. Apart from that, it is hoped that the integration of mathematics with Islamic values will form good Muslim personal character. Mathematics is a branch of science that has several characteristics, namely hierarchical or orderly, autonomous and consistent. This is of course closely related to the condition of Islamic values, one example of which is the prayer service which has one of the pillars, namely the pillars of meaning or order. A Muslim who performs prayer is certainly obliged to understand the pillars of prayer, including being orderly, if he intentionally leaves them, the prayer will be invalid. Related to orderliness, namely that it is carried out sequentially and consistently. This research aims to integrate Islamic values with lines and angles in mathematics. This research uses a literature study method with activity steps, namely reading and recording relevant and authentic sources, managing research materials, critically reviewing knowledge, ideas or findings in the literature and formulating specific theoretical and methodological contributions. The research results show that when a Muslim wants to stand perfectly in prayer, he forms an upright position in a straight line or forms a 180 angle0. Other movements in prayer, if observed, will form certain angles which, if added together, will form a full circle with a size of 3600. The results of the next study are that someone who is studying in class or at science councils will be shown to obtain angle measurements based on the level of knowledge they have. The context of degrees in mathematics means the measurement of angles depicted on a flat plane. This is in accordance with the quotation of the verse from the Qur'an, "Allah raises the rank of those who believe and have knowledge several degrees" (Mujadalah: 11).